2012
DOI: 10.1371/journal.pone.0052747
|View full text |Cite
|
Sign up to set email alerts
|

Using Bacteria to Determine Protein Kinase Specificity and Predict Target Substrates

Abstract: The identification of protein kinase targets remains a significant bottleneck for our understanding of signal transduction in normal and diseased cellular states. Kinases recognize their substrates in part through sequence motifs on substrate proteins, which, to date, have most effectively been elucidated using combinatorial peptide library approaches. Here, we present and demonstrate the ProPeL method for easy and accurate discovery of kinase specificity motifs through the use of native bacterial proteomes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…The clearly defined pattern of phosphorylation observed in the context of peptides harboring a fixed S/T phosphoacceptor sequence suggests that Ssp2 KAD /Smk1 is predominantly an S/T kinase and that Y kinase activity on random peptide substrates is undetectable. We also compared the sequences surrounding the phosphorylated peptides identified in the bacterial phosphoproteomic analysis by using a program that normalizes amino acid occurrence in the set of pT-and pS-containing phosphopeptides to the relative abundance in the proteome (pLogo) (23,24) (Fig. 6C; Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The clearly defined pattern of phosphorylation observed in the context of peptides harboring a fixed S/T phosphoacceptor sequence suggests that Ssp2 KAD /Smk1 is predominantly an S/T kinase and that Y kinase activity on random peptide substrates is undetectable. We also compared the sequences surrounding the phosphorylated peptides identified in the bacterial phosphoproteomic analysis by using a program that normalizes amino acid occurrence in the set of pT-and pS-containing phosphopeptides to the relative abundance in the proteome (pLogo) (23,24) (Fig. 6C; Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…23 His 6 /V5-tagged ATG16L1 expressed in E. coli was purified using Ni-NTA beads followed by CSNK2 treatment, and then analyzed for its association with purified ATG12-ATG5 conjugate. The results indicated that CSNK2 phosphorylation of ATG16L1 promoted its association with the ATG12-ATG5 protein complex, which was abolished by dephosphorylation of ATG16L1 by lPP (Fig.…”
Section: Csnk2 Was Responsible For Atg16l1 Phosphorylation In H/rtreamentioning
confidence: 99%
“…To bypass endogenous kinase activity, motifs were also revealed by mass spectrometry for recombinant serine/threonine kinases PKA and CK2 expressed in bacteria (Chou et al, 2012). Utilizing experimentally derived motif data, a variety of computational approaches for scoring linear kinase motifs in the proteome to predict putative substrate sites have been developed (Miller et al, 2008;Xue et al, 2008;Hu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%